2007
DOI: 10.1099/jmm.0.46833-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies to Pseudomonas aeruginosa in serum and oral fluid from patients with cystic fibrosis

Abstract: Cystic fibrosis (CF) patients who are chronically infected with Pseudomonas aeruginosa make serum antibodies to bacterial surface LPS as well as other pseudomonas antigens. This study investigated the feasibility of using oral fluid samples for the detection of pseudomonas antibodies in CF patients and compared these results with corresponding serum antibodies. Most strains of P. aeruginosa produce two forms of LPS molecule, termed A-band (described as a common antigen) and B-band (O-serotype-specific antigen)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…The strains that did not react to the mAb belong to serotypes O7, O12, O13, O14, O15, and O16 (Lam et al, 1989; Currie et al, 1995). However, a majority of clinical P. aeruginosa isolates examined since then were found to be devoid of OSA but produce CPA as the predominant surface polysaccharide antigen (Lam et al, 1989; Weisner et al, 2007). In a separate study, CPA was found to be a receptor for bacteriophage A7, indicating its significance as a cell-surface polysaccharide component of P. aeruginosa and its role in the co-evolution with temperate bacteriophages (Rivera et al, 1992).…”
Section: Structure Genetics and Function Of Cpa (A Band)mentioning
confidence: 99%
“…The strains that did not react to the mAb belong to serotypes O7, O12, O13, O14, O15, and O16 (Lam et al, 1989; Currie et al, 1995). However, a majority of clinical P. aeruginosa isolates examined since then were found to be devoid of OSA but produce CPA as the predominant surface polysaccharide antigen (Lam et al, 1989; Weisner et al, 2007). In a separate study, CPA was found to be a receptor for bacteriophage A7, indicating its significance as a cell-surface polysaccharide component of P. aeruginosa and its role in the co-evolution with temperate bacteriophages (Rivera et al, 1992).…”
Section: Structure Genetics and Function Of Cpa (A Band)mentioning
confidence: 99%
“…The strains that did not react to the MAb were of serotypes O7, O12, O13, O14, O15, and O16 (19,20). It is worth noting that the majority of clinical P. aeruginosa isolates from chronically infected cystic fibrosis patients lack OSA but produce CPA as the predominant surface polysaccharide antigen (19,21). CPA biosynthesis genes are organized into two contiguous clusters, an eight-gene operon consisting of rmd, gmd, wbpW, wzm, wzt, wbpX, wbpY, and wpbZ (pa5454-pa5449) (22)(23)(24) and a newly identified, five-gene operon, pa5455-pa5459, in PAO1 (25) (Fig.…”
mentioning
confidence: 99%
“…Another group of authors, seeking to establish whether it would be possible to use saliva as a tool for the detection of anti-P. aeruginosa antibodies in patients with CF and in normal individuals,( 29 ) described significant titers in the oral fluids from 15 of the 17 patients with CF but in none from the healthy volunteers (LE 2b).…”
Section: Methodsmentioning
confidence: 99%
“…Outro grupo de autores procurou avaliar se seria possível utilizar a saliva como um instrumento de detecção de anticorpos anti- P. aeruginosa em pacientes com FC e em indivíduos normais,( 29 ) descrevendo títulos significativos nos fluidos orais de 15 dos 17 pacientes com FC, mas em nenhum dos voluntários sadios (NE 2b).…”
Section: Métodosunclassified